(untitled) (Journal of Management and Social Sciences, 2021)
The most important determinant of saving is the level of income. Higher levels of savings can translate to higher levels of investment and rural development. To boost income, rural women diversify their livelihood activities. This study examined income diversification and savings pattern among rural women in Oyo State, Nigeria. Various income-generating activities, patterns of diversity and savings, determinants of income diversification and saving rate, and the effect of income diversification on rural women savings were assessed. Structured questionnaire was administered on a sample of 204 rural women who were selected using multi-stage sampling procedure. Descriptive statistics, Simpson diversity index and Tobit regression models were used in data analysis. Results show that majority (75%) of the rural women were arable crop farmers and 96% were diversified in income generation. The mean diversity index was 0.44, implying that on the average, rural women engaged in more than one income-generating activities. Saving rate is relatively low with mean saving rate of 28.08%. Tobit regression results show that membership of cooperative society (p<0.05), credit received (p<0.1) and road network (p<0.01) significantly affect income diversification. Also, income diversification (p<0.05), total income (p<0.01), household size (p<0.01) and age (p<0.01) significantly affect savings rate. Having more than one source of income increases saving rate among rural women. Therefore, Government and Non-governmental organizations (NGOs) should assist in making credit facilities available to rural women and ensure adequate monitoring to prevent diversion of funds, provide social amenities and organize training to improve production processes among rural women. Keywords Income diversification, savings pattern, savings rate, rural women, saving mode